Dinamika Hasrat Narsistik dalam Cerpen Tiurmaida Karya Hasan Al-Banna: Kajian Psikoanalisis Jacques Lacan - Nursalassaty; Hadawiyah, Andina; Ulfa, Syafrina; Shite, Yohan Tio Pantaria; Arianto, Tomi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the structure of desire of the main character in the short story